Inserção e proximidades: mediação em espaços culturais para alunos da educação de jovens e adultos - Leonardo Pereira Maia (2016)
This study describe the pedagogical proposal for inclusion of the student audience of the Youth and Adult Education School Belizário Ferreira Caminhas, located in Betim / MG, to cultural spaces in the metropolitan region of Belo Horizonte. Considering the specificity of the EJA students, sought to build reflections on on the Art classes can contribute to the experience and access that audience to these spaces, while that is reflected on the possible contributions that such places may offer to the teaching / learning process student body art in question.